Tinjauan Kompilasi Hukum Islam Terhadap Status Harta Warisan Anak Angkat - Ahmad Hafid Safrudin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
The realm of life for adopted children in the midst of today's society is a rare phenomenon and certainly a clear law is needed, and it seems to be a problem that is quite interesting to be discussed in today's scientific traditions. The child is a mandate from the almighty God, given so that it can be nurtured by birth and birth by the family. A child is indeed worthy of living with all the needs that both biological parents strive for, because it is his responsibility. However, this situation often cannot be felt by some children who are likely because one or both parents have not been around (died). This possibility causes the child's life situation to no longer be like that of another child, who still has biological parents. However, there can also be a possibility because both biological parents are indeed economically unable to afford the child's life. Several other reasons can also occur, so that by other families the child is then taken to be an adopted child. Related in this study, that the existence of the adopted son mentioned above has a position on the inheritance property. According to Islamic law, although clearly Islam cannot accept the existence of an adopted child for his position towards the estate of the adoptive parents. However, the KHI, which in fact is a written law that is enforced as a special guideline for Muslims in resolving all legal issues including regarding the position of the adopted child, in article 209 of the KHI explains that the adopted child is entitled to receive a mandatory will of as much as 1/3 of the adoptive parents' estate.